Individual effects of atmospheric water vapor and carbon dioxide on the kinetics of the thermal decomposition of granular malachite. Issue 18 (26th April 2022) - Aoki, Yuta; Koga, Nobuyoshi
Abstract : The physico-chemical and physico-geometrical characteristics of the thermal decomposition of solids should be considered when interpreting the effects of atmospheric conditions on the kinetics. Abstract : This study examined the effects of atmospheric water vapor and CO2 on the thermal decomposition of granular malachite as a model process for the thermal decomposition of large and compact agglomerate solids. In previous studies in a dry N2 gas stream, the thermal decomposition of the granular malachite exhibited physico-geometrically constrained two-step mass loss behaviors accompanied by the swelling of granular particles and crack formation in the surface product layer of each granule. In the presence of atmospheric water vapor, the reaction was shifted systematically to lower temperatures with increasing atmospheric water vapor pressure ( p (H2 O)) by maintaining the two-step mass loss behavior. Kinetic analyses of the two-step heterogeneous process and subsequent universal kinetic description for each reaction step over different p (H2 O) values demonstrated that the catalytic effect of atmospheric water vapor is more significant in the first reaction step because of the surface reaction. Conversely, in the presence of atmospheric CO2, the reaction shifted systematically to higher temperatures with increasing partial pressure of CO2 where the surface and internal reaction steps were more clearly separated, and additional mass-loss steps appeared to complete the reaction. The enhanced retardation effects of atmospheric CO2 as the mass-loss process advanced were confirmed by kinetic analyses of the empirically deconvoluted five-step reaction process. This phenomenon was explained by the effects of atmospheric CO2 on the construction of the surface product layer that helps block the diffusional removal of the gaseous product and increases the internal gaseous pressure.